Kesadaran Berempati Terhadap Perundungan Melalui Storytelling pada SDN 10 Tanjung Lago - Hurriyati, Dwi; Mega Wulansari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This Community Service Program aims to enhance students' empathetic awareness of bullying behavior at SD Negeri 10 Tanjung Lago through the storytelling method. Based on initial observations, a phenomenon of playful teasing was found, which students often misinterpret, indicating low awareness of the psychological impact of such actions. The intervention was carried out in three main stages: (1) interactive storytelling using the educational comic "Jendela Hati", (2) an educational word-search game with an anti-bullying theme, and (3) an evaluation of understanding and measurement of empathy using a checklist scale. The results showed active participation and enthusiasm from the students. Data from the empathy scale involving 30 fifth-grade students revealed that 90% of respondents fell into the high and very high empathy categories, with a distribution of 60% (very high) and 30% (high). These findings indicate that although cognitively the students already possess a strong foundation of empathy, its application in daily social interactions still requires guidance to distinguish between teasing and bullying. The program concludes that storytelling is effective as an educational medium for fostering empathetic awareness, improving understanding of various forms of bullying, and encouraging prosocial attitudes in the school environment, thereby contributing to the creation of a safer and more inclusive school climate.